2010
DOI: 10.1088/0953-8984/22/47/474010
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Yb nanoparticle thin films grown by deposition in He and N2gas atmospheres: AFM and x-ray reflectivity studies

Abstract: Nanoparticles of lanthanide metals and their compounds are important from the viewpoint of both basic research and application to many functional devices. In the present work, a gas deposition technique was employed to prepare thin films composed of ytterbium (Z = 70) nanoparticles on a glass substrate. The influence of deposition conditions such as deposition temperature, time and gas pressure was studied in detail. In addition to an ordinary inert gas such as He, the possible use of N(2) was investigated. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…, f-c-c structure) of Yb were synthesized previously by the bio-reduction method to generate high metal content, particularly as blood pool agents. 16 However, their large size ( i.e. , >6 nm, the renal clearance threshold and resultant poor biological elimination poses potential issues regarding long-term safety, similar to the barriers facing quantum dots or carbon nanotubes (SWNT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, f-c-c structure) of Yb were synthesized previously by the bio-reduction method to generate high metal content, particularly as blood pool agents. 16 However, their large size ( i.e. , >6 nm, the renal clearance threshold and resultant poor biological elimination poses potential issues regarding long-term safety, similar to the barriers facing quantum dots or carbon nanotubes (SWNT).…”
Section: Resultsmentioning
confidence: 99%
“…Metal clusters (e.g., fcc structure) of Yb were synthesized previously by the bioreduction method to generate high metal content, particularly as blood pool agents. 16 However, their large size (i.e., >6 nm), the renal clearance threshold, and resultant poor biological elimination pose potential issues regarding long-term safety, similar to the barriers facing quantum dots or carbon nanotubes (SWNT). Very recently, Lu et al reported an Yb-based nanoparticle stabilized with oleic acid and modified with the biocompatible polymer DSPE-PEG 2000 for conventional CT imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparatus used for the preparation of the thin film was the MBE setup, equipped with a substrate-cooling system, that was specifically designed for formation of metallic nanoparticles. 31 The system has two separated rooms; one is a load-lock chamber for exchanging the samples, and the other one is a main chamber, where the ultrahigh vacuum conditions are always maintained. The temperature of the Knudsen (K) cell in the cell container was controlled by electric heating.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%